2011
DOI: 10.1155/2011/195037
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CT-Based Attenuation Correction and Collimator Blurring Correction in Striatal Spect Quantification

Abstract: Purpose. Striatal single photon emission computed tomography (SPECT) imaging of the dopaminergic system is becoming increasingly used for clinical and research studies. The question about the value of nonuniform attenuation correction has become more relevant with the increasing availability of hybrid SPECT-CT scanners. In this study, the value of nonuniform attenuation correction and correction for collimator blurring were determined using both phantom data and patient data. Methods. SPECT imaging was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
1
6
0
1
Order By: Relevance
“…However, Chang AC resulted in larger SBRs than CT-based AC even with LAC as low as µ = 0.10 cm −1 (LAC for CT-based AC fixed at µ = 0.148 cm −1 ). Warwick and co-workers also found larger SBRs in dopamine transporter SPECT with Chang AC than with CT-based AC, at least in the patient scans included in their study [35] . Rajeevan et al evaluated non-uniform AC based on transmission imaging for I-123-β-CIT and concluded that both non-uniform and uniform AC provide a small improvement of semi-quantitative analysis compared to no AC [36] .…”
Section: Discussionmentioning
confidence: 72%
“…However, Chang AC resulted in larger SBRs than CT-based AC even with LAC as low as µ = 0.10 cm −1 (LAC for CT-based AC fixed at µ = 0.148 cm −1 ). Warwick and co-workers also found larger SBRs in dopamine transporter SPECT with Chang AC than with CT-based AC, at least in the patient scans included in their study [35] . Rajeevan et al evaluated non-uniform AC based on transmission imaging for I-123-β-CIT and concluded that both non-uniform and uniform AC provide a small improvement of semi-quantitative analysis compared to no AC [36] .…”
Section: Discussionmentioning
confidence: 72%
“…The mean CT effective dose was 0.36 mSv and the increase in radiation dose was very low at 3.2%. In addition to attenuation correction and added anatomical information for DAT-SPECT [ 28 30 ], our study demonstrated that CT can be used to guide ROI delineation for semiquantifying striatal DAT availability. It may also justify the extra radiation dose from CT.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, Warwick et al studied phantoms and 14 patients and showed that AC improved the quantitation of striatal SPECT images of the phantom, and AC also optimized patients' brain SPECT reconstruction. 11 Another parameter in interpreting 123 I-FP-CIT SPECT is the asymmetric index (AI) value to evaluate the asymmetry of radioligand uptake. 12 The aim of this study was to evaluate the influence of AC and SC on the quantitative analysis of 123 I-FP-CIT SPECT brain imaging in both phantom and clinical studies.…”
Section: Resourcesmentioning
confidence: 99%